STUDY OF THE ECONOMIC SITUATION OF ARMENIA AND ARRAN DURING THE 10th CENTURY AD - Горбаннежад, Париса (History, Archeology and Ethnography of the Caucasus, 2025)
The study of medieval Islamic lands’ social and economic conditions is central to understanding the history of Islamic civilization. Arran and Armenia, as frontier regions of the Islamic world, retained significant political and economic importance during the 10th century. This study examines the economic conditions of Arran and Armenia in the 10th century, focusing on their production and trade. Analysis of written sources reveals that economic activity flourished under the rule of the Sajid (889–930 CE), Sallarid (941–980 CE), and Rawwadid (981–1071 CE) dynasties, which controlled much of Arran and Armenia. Policies such as minting coins, reducing taxes and tributes, and fostering relations with local rulers led to increased agricultural, livestock, and industrial production, driving economic growth in these regions. Furthermore, the establishment of international markets and the availability of diverse goods facilitated exports to other regions and the importation of essential commodities for Islamic lands. Through trade expansion, Arran – and particularly Armenia – emerged as a vital commercial hub within the Islamic world. Consequently, the strategic use of abundant natural resources and favorable trade conditions enabled local populations to meet their daily needs and sustain economic activities, despite the disruptions caused by warfare.